Predicting future lifetime for mixture exponential distribution. Issue 7 (3rd July 2022) - Barakat, H. M.; Khaled, O. M.; Ghonem, Hadeer A.
Abstract: This paper studies the prediction problem of future order statistics based on a mixture of exponential distributions. We suggest different scenarios to construct predictive intervals and point predictions for the future observations in two cases. In the first case, we assume fixed sample size, while in the second case, the sample size is assumed to be positive integer–valued random variable independent of the observations.